Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica - Rodiles-Hernández, Rocío; Hendrickson, Dean A.; Lundberg, John G.; Humphries, Julian M. (Zootaxa, 2005)
A new family (Lacantuniidae), genus and species of catfish, Lacantunia enigmatica, is described from the Río Usumacinta basin of Chiapas, México. This odd siluriform is diagnosed by five distinctively autapomorphic and anatomically complex structures. The fifth (last) infraorbital bone is relatively large, anteriorly convex and remote from a prominent sphenotic process. The lateral margin of the frontal, lateral ethmoid and sphenotic bones are thick at the origins of much enlarged adductor mandibulae and levator arcus palatini muscles; otherwise the skull roof is constricted and flat. One pair of cone-shaped "pseudo-pharyngobranchial" bones is present at the anterior tips of enlarged cartilages medial to the first epibranchial. A hypertrophied, axe-shaped uncinate process emerges dorsally from the third epibranchial. The gas bladder has paired spherical, unencapsulated diverticulae protruding from its anterodorsal wall. Lacantunia enigmatica cannot be placed within or as a basal sister lineage to any known catfish family or multifamily clade except Siluroidei. This species may represent an ancient group, perhaps of early Tertiary age or older, and it adds another biogeographic puzzle to the historically complex Mesoamerican biota.